A representation of specular appearance - Lin, Steve; Lee, Sang W. (International Conference on Computer Vision (ICCV), 1999)
The appearance of an object can vary considerably with changes in illumination conditions. Methods have been developed to describe these differences for diffuse reflection using the Lambertian model, but little work has been done in characterizing specular appearance. Towards a more comprehensive global reflectance descriptor, this paper focuses on a representation of specular appearance based on an approximate specular reflection model derived from Torrance-Sparrow. We propose that under certain illumination and surface conditions local specular structure can be expressed by the logarithms of three intensity-normalized photometric images. The total number of photometric images needed for representing global specular appearance depends on the object surface roughness, and we suggest an illumination planning method for determining the number of images. Experimental results demonstrate the effectiveness of this logarithmic model as a specular descriptor.